Effect of Peer-Tutoring Learning Teaching Method on Academic Performance of Financial Accounting Students in Federal Unity Colleges, in North-Eastern Nigeria (Journal of Advanced Research in Social Sciences, 2018)
This study established the effect of peer tutoring teaching method on students’ performance in financial accounting in Federal unity Colleges of in North-East, Nigeria. The study had three objectives, three research questions, and three null hypotheses. A quasi-experimental design was used for the study. The population of the study was 130 SS II Financial Accounting students. An intact two classes of 46 students were used for the study. Two instruments were used for data collection were validated by four experts. The instrument had a coefficient of 0.87 and 0.89. The difficulty index of instruments stood at 0.76 and 0.81. The discriminating index of the items ranges from 0.5 to 0.7. Data collected were analyzed using mean and mean difference to answer the research questions. The t-test was employed in testing the hypotheses at 0.05 level of significance. The findings revealed among others that there was a significant difference between the mean performance of financial accounting students in the experimental group and those in the control group. It was concluded that using of peer tutoring strategy will help to improve the performance of financial accounting students. It was recommended among others that, accounting teachers should develop a habit of using interactive methods which allows students to actively participate in the teaching and learning excise.